Efektivitas edukasi melalui modul ha-man terhadap efikasi diri kelompok usia dewasa dalam mencegah penyakit jantung koroner: Effectiveness of education using ha-man module on self-efficacy of adults in preventing coronary heart disease - Suarningsih, Ni Kadek Ayu; Saputra, I Kadek (Bali Medika Jurnal, 2021)
Every year, there is a significant increase in deaths caused by coronary heart disease (CHD). Many programs have been implemented to reduce the morbidity and mortality of CHD. Early detection and control of CHD risk factors is a challenge in educating adults about lifestyle changes. Also, it is recognized that self-efficacy is a vital factor in initiating and maintaining healthy behaviors. Health education is given as an effort to increase self-efficacy, but educational media that are innovative in promoting CHD health are limited. This study aimed to determine differences in the self-efficacy of adults in preventing coronary heart disease before and after given health education. This was a quasi-experimental study with a pretest-posttest control group design. The sample were 60 respondents which were grouped into 30 respondents in the intervention group and control group through purposive sampling. The HA-Man education intervention was given 3 times for a-week, self-efficacy was evaluated through a structured questionnaire interview. The results showed that there were differences in self-efficacy before and after intervention in the intervention group (p <0.05). This research is expected to provide information in the development of educational media in increasing awareness and self-efficacy of people who are at risk of CHD